Mengeksplorasi Persepsi Siswa Terhadap Penggunaan Teknologi dalam Pembelajaran - Adilah Mazaya Nabilah (STAI AL-AMIN, 2025)
This article explores students' perceptions of the use of technology in learning at Madrasah Ibtidaiyah (MI). With the rapid development of information and communication technology, the integration of technology in education is becoming increasingly important. This research aims to understand how students perceive the effectiveness of technology in helping them understand lesson concepts, as well as the challenges faced in its implementation. The methods used in this research include surveys and interviews with students at several MI. The results showed that students had diverse views; most felt that technology enhanced their interest and understanding, while others experienced distractions and difficulty accessing it. This article also identifies the negative impacts of technology use, such as dependency and lack of social interaction. The conclusions of this research emphasize the importance of training for teachers and developing relevant curricula to maximize the benefits of technology in learning. Suggestions are provided for improving access to technology and conducting further research on student perceptions in different contexts.